Modulation of sodium iodide symporter expression and function by LY294002, Akti-1/2 and Rapamycin in thyroid cells - Liu, Yu-Yu (2012)
The selective increase of Na(+)/I(−) symporter (NIS)-mediated active iodide uptake in thyroid cells allows the use of radioiodine I(131) for diagnosis and targeted treatment of thyroid cancers. However, NIS-mediated radioiodine accumulation is often reduced in thyroid cancers due to decreased NIS expression/function. As PI3K signaling is overactivated in many thyroid tumors, we investigated the effects of inhibitors for PI3K, Akt, or mTORC1 as well as their interplay on NIS modulation in thyroid cells under chronic TSH stimulation. PI3K inhibition by LY294002 increased NIS-mediated radioiodide uptake (RAIU) mainly through upregulation of NIS expression, however, mTORC1 inhibition by Rapamycin did not increase NIS-mediated RAIU despite increased NIS protein levels. In comparison, Akt inhibition by Akti-1/2 did not increase NIS protein levels, yet markedly increased NIS-mediated RAIU by decreasing iodide efflux rate and increasing iodide transport rate and iodide affinity of NIS. The effects of Akti-1/2 on NIS-mediated RAIU are not detected in nonthyroid cells, implying that Akti-1/2 or its derivatives may represent potential pharmacological reagents to selectively increase thyroidal radioiodine accumulation and therapeutic efficacy.